Pengaruh Model Pembelajaran Value Clarification Technique (VCT) Terhadap Sikap Nasionalisme Peserta Didik Dalam Pembelajaran PKN - Nabila Cahyaningtiyas; Winti Ananthia; Yayang Furi Furnamasari (Jurnal Bintang Pendidikan Indonesia, 2023)
In the current era of globalization, foreign cultures can enter freely and influence students so that the value of nationalism in students fades, this is indicated by the behavior of students who deviate from the objectives of national education, especially when the teacher does not innovate the learning model used can cause students to be bored during learning. This study aims to determine the effect of the VCT learning model on the nationalism attitude of students and the difference in increasing the attitude of nationalism between classes using the VCT model and classes using conventional methods. This research uses a quasi-experimental method with a quantitative approach using a Non-equivalent control group design, the subjects of this research are students of grades VA and VB SDN Pantai Bahagia 01 in the 2022/2023 school year. The instruments used in this research are observation, test and questionnaire. The results of this study indicate that the effect of the VCT model on the nationalism attitude of students can be seen from the N-Gain test which states that the experimental class obtained the N-Gain value in the medium category, meaning that it experienced a moderate increase, while the control class obtained the N-Gain value in the low category, meaning that it did not experience an increase. The difference in improvement can be seen from the average value of the pretest and posttest of the experimental class which is greater than the control class supported by the mann whitney test which states that there is a difference in increasing the attitude of nationalism between the experimental class and the control class.